A Chromogenic Test to Determine the Procoagulant Phospholipids in Platelet-rich Plasma and Whole Blood - Wagenvoord, R J; Hendrix, H H; Kai, Hu; Hemker, H C (Thrombosis and Haemostasis, 1994)
We have developed a chromogenic assay to measure the phospholipid-related procoagulant activity (PPA) in whole blood, or platelet-rich plasma. The test is based upon thrombin formation from prothrombin by prothrombinase and is designed in such a way that procoagulant lipids are rate limiting for the prothrombinase activity. In the chromogenic test PPA concentrations equivalent to 0-10 nM phospholipid vesicles containing 75% phosphatidyl choline (PC) and 25% phosphatidyl serine (PS) can be measured.The thrombin, which develops during the test, is measured with a chromogenic substrate. By the action of thrombin on this chromogenic substrate p-nitroaniline is liberated, which causes an increase in absorbance. Thrombin formed in the assay mixture activates the present platelets. This causes a linear increase of the velocity of thrombin generation during the test, i. e. a parabolic increase of product formation. For that reason the thrombin generation in time is characterized by two parameters, the basal PPA (PPA-B) of the original mixture and the increase in PPA due to platelet activation (PPA-A). To determine these figures the absorbency-data were fitted to parabolas. In most cases the contribution of PPA-A to the total amount of formed thrombin becomes considerable already after 30 s.Preliminary tests show that PPA-B activity in whole blood or platelet-rich plasma of patients with a thrombotic disorder is significantly higher than the activity of a control group of the same age.